The epistemology, ontology, and axiology of psychology from Islamic perspectives - Abdul Rahman, Shukran (2018)
BACKGROUND Scholars have been found to use various approaches and methods when studying subject matters in Psychology, and the subject matter-in questions differ from one scholar to another. It has been found that both the former, which concerns the epistemological aspect of Psychology; and the latter (ontological aspects) have been influenced by cultural factors, including the belief systems of the scholars and their disciples (axiological aspects). OBJECTIVES The objective of this paper is to discuss the nature of human characteristics (ontological aspects); the ways to study them (ontological aspects), and the underlying principles which govern the process to, and scope of, the study of human characteristics (axiological aspects) by highlighting the contributions of Bediüzzaman Said Nursi to the field of Psychology. METHOD This paper attempts to address the objectives by adopting the Kipling method of collecting and analysing information (Miller, 2009). It helps the authors to analyse relevant information obtained from various literature which feature Said Nursi and his work. SIGNIFICANCE This paper highlights the contribution of Said Nursi in the study of Psychology, offering an alternative avenue to the Western perspective of Psychology. It also features the roles of Muslim scholars in describing the nature of human being and the ways they derive the knowledge.